2021
DOI: 10.1186/s12913-021-06665-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of the public and private health sectors on factors associated with early essential newborn care practices among institutional deliveries in Ghana

Abstract: Background Early essential newborn care is one of the important interventions developed by the World Health Organization to reduce morbidities and mortalities in neonates. This study investigated the role of the public and private sector health facilities on factors associated with early essential newborn care practices following institutional delivery in Ghana. Methods We used data from the 2017/2018 multiple indicator cluster survey for our analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
2
1
Order By: Relevance
“…The public sector had significantly higher levels for immediate breastfeeding and skin-to-skin contact, while the private sector has higher levels of adherence to all other ENC and PNC indicators, with the exception of observing breastfeeding during the PNC check, which was similar in both sectors. This finding differs from studies in Ghana and Eastern Uganda that found that public sector providers performed better than private providers in provision of essential newborn care [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The public sector had significantly higher levels for immediate breastfeeding and skin-to-skin contact, while the private sector has higher levels of adherence to all other ENC and PNC indicators, with the exception of observing breastfeeding during the PNC check, which was similar in both sectors. This finding differs from studies in Ghana and Eastern Uganda that found that public sector providers performed better than private providers in provision of essential newborn care [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 98%
“…The public and private sectors are both important sources for reproductive, maternal, and child health services [ 18 20 ], yet few studies have examined the quality of newborn care in the private sector and how it differs from the quality of care provided in the public sector and at home. We could identify only two studies that examined adherence to essential newborn care guidelines in the private sector; one focused on a single country and the other on a single region within a country [ 21 , 22 ]. Understanding how well and where ENC, PNC, and sick neonatal care are provided across countries is critical to catalyzing progress across sectors and achieving high quality neonatal care for all.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to analysis, each set of data underwent a meticulous verification process to ensure both its integrity and precision. The study's conclusive sample encompassed 484 staff members, which equates to a 69% participation rate, a figure that comfortably meets the benchmark for statistical evaluation as established [63]. To maintain uniformity across the collected data, a coding system was implemented for the questionnaires to align with the responses provided by the employees.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Private providers or private health insurance are perceived better in providing perceived quality of services. Those who have health insurance or have access to public healthcare providers have a higher chance of receiving care [5,6]. The right combination of public and private roles in ensuring access to healthcare and eliminating financial hardship in meeting healthcare needs is a big challenge to achieving universal health coverage (UHC) in many developing countries.…”
Section: Introductionmentioning
confidence: 99%